The Effect of Sharia Financial Liquidity and Intermediation on Profitability: ECM Panel Study on BUS and UUS in Indonesia - Gita Danu Pranata; Agus Tri Basuki (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of liquidity and Islamic financial intermediation on the profitability of Sharia Commercial Banks (BUS) and Sharia Business Units (UUS) in Indonesia. The variables used include profitability as a dependent variable, while liquidity is proxied with cash, and Islamic financial intermediation is proxied with Third Party Funds (DPK) and profit-sharing financing. The research uses monthly panel data from BUS and UUS for the period January 2023–January 2026. The analysis method used is the Panel Error Correction Model (Panel ECM) to identify short-term and long-term relationships between variables. The results of the unit root test showed that all variables were integrated in the first order, while the cointegration test confirmed the existence of a long-term relationship between the study variables. The results of long-term estimation show that cash, deposits, and profit-sharing financing have a positive effect on profitability. These findings indicate that increasing liquidity and optimizing the function of sharia intermediation can improve the profitability performance of Islamic banking. In addition, the existence of an adjustment mechanism towards a long-term equilibrium shows that the profitability of BUS and UUS has the ability to return to equilibrium after economic shocks. This research provides important implications for Islamic bank management in managing liquidity and strengthening the intermediation function to increase profitability in a sustainable manner.